Denying bogus skepticism in climate change and tourism research. (April 2015) - Hall, C. Michael; Amelung, Bas; Cohen, Scott; Eijgelaar, Eke; Gössling, Stefan; Higham, James; Leemans, Rik; Peeters, Paul; Ram, Yael; Scott, Daniel; Aall, Carlo; Abegg, Bruno; et al.
Abstract: This final response to the two climate change denial papers by Shani and Arad further highlights the inaccuracies, misinformation and errors in their commentaries. The obfuscation of scientific research and the consensus on anthropogenic climate change may have significant long-term negative consequences for better understanding the implications of climate change and climate policy for tourism and create confusion and delay in developing and implementing tourism sector responses. Highlights: Final Response to claims of Shani and Arad (2014, 2015). Extent of scientific consensus on climate change indicated. Evidence for climate change is observational and predictive. Extent of tourism related emissions indicated. Concern over climate denial for scientific debate and communication.